Personal and socio-psychological characteristics of women of reproductive age, operated on for symptomatic endometriod desease, at the stage of pregnancy planning - T. P. Chuieva-Pavlovska; I. Z. Gladchuk; O. M. Nosenko (Kazimierz Wielki University, 2017)
Endometrioid disease occurs in every tenth woman of reproductive age and often leads not only to physical discomfort, but also frustrates them psychosocially, reduces professional, psychosocial and reproductive adaptation in general. The aim: to reveal the personal and psychosocial characteristics of women at the stage of pregnancy planning, operated on for symptomatic endometriosis, in connection with the task of optimizing the management and improvement of pregnancy outcomes. Material and methods. Under observation, there were 123 women operated on for symptomatic endometriosis, 125 somatically and gynecologically conditionally healthy fertile women. All the women were going to plan a pregnancy. The diagnosis of endometriosis in all cases was identified histologically. The psychosocial and personal characteristics of these women at the stage of pregnancy planning were studied. Conclusions.  The peculiarities of the personal and psychosocial characteristics of women at the stage of pregnancy planning, operated on for symptomatic endometriosis, are unfavorable child-parent relations, destructive relationships with their own mother, complicated course of pregnancy in the mother, high personal anxiety, impaired sex and age identification in women, inadequate (infantile, disadaptive) forms of responding to stressful situations, emotional instability.